Prevalence and Characterization of Some Colibactin Genes in Clinical Enterobacteriaceae isolates from Iraqi Patients (Baghdad Science Journal, 2020)
The members of the family of Eentrobacteriaceae harbour a gene cluster called polyketide synthase (pks) island. This cluster is responsible for the synthesis of the genotoxin colibactin that might have an important role in the induction of double-strand DNA breaks, leading to promote human colorectal cancer (CRC). Eleven out of the eighty eight isolates (12.5%) were pks+, distributed as 7 (8%) isolates of E. coli, 2 (2.25%) of K. pneumoniae and 2 (2.25%) of E. aerogenes. The cytotoxic effects of selected pks+ isolates (E. coli and E. aerogenes) on HeLa cells were represented by decreasing cell numbers and enlarged cell nuclei in comparison to the untreated cells. Cytological changes were observed when the infected HeLa cells cultures were stained with AO/EBr and visualized under fluorescent microscope. Some changes that happened in the color of the nuclear chromatin were accompanied by DNA condensation and degradation and fragmentation of nuclei. HeLa cells with green unchanged nuclear chromatin were alive while those with orange-dark and bright red nuclei were dead. It was concluded that a proportion of the Entreobacteriaceae isolates from Iraqi patients was pks+, which exerted cytotoxic effects upon using them to kill HeLa cells. In this study the microscopic observation of the cell morphology reveals the cellular response to the genotoxic insult, with reduced numbers, striking giant cells phenotype (megalocytosis) and fragmentation of nuclei due to the cell cycle arrest and cellular senescence